Developing A Predictive Model for Small Business Loan Default - Refiloe Gladys Benedict; O Stumke; Veruschka Pelser Carstens (Journal of Accounting and Finance in Emerging Economies)
Purpose: Governments assume responsibility for supporting SBs, including financial assistance. In South Africa, legislative measures and strategic initiatives have been established to bolster SBs, including the creation of funding agencies. These agencies intervene to enhance SB growth, job creation, poverty reduction, increased tax revenue and overall economic participation. This inherent risk results in ongoing losses and suboptimal returns on government investments, potentially wasting taxpayer funds. This paper proposes a model aimed at proactively increasing loan repayment probabilities. The study investigates SB characteristics that can pre-emptively mitigate loan repayment failures to government agencies.